HERBAL WEALTH FOR HEPATOTOXICITY: A REVIEW - N, Himaja; S, Neelufar Shama (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Liver is the prominent organ of biliary system and it is one of the vital organs involved in various responsibilities required to maintain homeostasis of our body. It has got its own vital role in the physiological system. Metabolism of ingested substances such as carbohydrates, lipids, proteins, blood coagulation, and immunomodulation are the primary functions of the liver. 1 out of 3 peoples are affected by liver diseases. Around more than 2000 billion people alive with affecting hepatotoxicity. The synthetic drugs to treat liver disorders also cause further damage to the liver. Hence, the popularity of herbal drugs is increasing and their use is wide-spread. Numerous medicinal plants are available to treat hepatoxicity some of the plants are Abrus precatorius, Abutilon indicum, Allium cepa, Andrographis paniculata, Averrhoa carambola, Azadirachta indica, Boerhavia diffusa, Cassia fistula, Curcuma longa, Daucus carota, Eclipta prostrata, Ficus carica, Homalomena aromatica, Indigofera barberi, Lawsonia inermis, Plumbago zylanica, Tamarindus indicus. The hepatotoxicy of various plants is evaluated by various liver cell injury inducing agents viz., chemicals such as carbon tetrachloride, ethanol; drugs such as ibuprofen, paracetamol, thioacetamide, ranitidine, anti-tubercular drugs; metals like cadmium, lead and the activity was estimated by parameters like serum glutamic pyruvic transaminase, serum glutamic oxaloacetic transaminase, aspartate amino transaminase, alkaline phosphatase, alanine amino transaminase, total cholesterol and bilirubin levels. The present review focused on different medicinal plants that have been tested in hepatotoxicity in animal models. Keywords: Liver, Hepatotoxicity, Herbal drugs, Abrus precatorius, Curcuma longa, Paracetamol, Serum glutamic pyruvic transaminase, Serum glutamic oxaloacetic transaminase.